2023
DOI: 10.5713/ab.22.0252
|View full text |Cite
|
Sign up to set email alerts
|

Iron sulfate and molasses treated anthocyanin-rich black cane silage improves growth performance, rumen fermentation, antioxidant status, and meat tenderness in goats

Abstract: Title of the manuscript: Iron sulfate and molasses treated anthocyanin-rich black cane silage improves growth performance, rumen fermentation, antioxidant status, and meat tenderness in goats ABSTRACTObjective: To investigate the effects of feeding anthocyanin-rich black cane treated with ferrous sulfate and molasses on animal performance, rumen fermentation, microbial composition, blood biochemical indices, and carcass characteristics in meat goats.Methods: Thirty-two Thai-native × Anglo-Nubian crossbred male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Gerber et al stated that the benefits of tannins consumption corresponded to reductions in N 2 O emissions and may have had an effect on H 2 S production ( 2 ). The H 2 required for the formation of CH 4 and H 2 S could have been used by other microbes or disposed in a sink ( 2 , 58 ). Therefore, our results demonstrate a synergistic effect of the combination of phytochemicals in Mix.…”
Section: Discussionmentioning
confidence: 99%
“…Gerber et al stated that the benefits of tannins consumption corresponded to reductions in N 2 O emissions and may have had an effect on H 2 S production ( 2 ). The H 2 required for the formation of CH 4 and H 2 S could have been used by other microbes or disposed in a sink ( 2 , 58 ). Therefore, our results demonstrate a synergistic effect of the combination of phytochemicals in Mix.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of legumes is not only determined by their nutrient contents, but also by the anti-nutritional compounds. Anti-nutritional compounds contained in lamtoro have been reported by Vahedi et al (2021) and Purba et al (2022), it was stated that mimosine is an antinutritional compound found in lamtoro. In addition, the study (Niyigena et al 2021) reported mimosa and excess blood urea nitrogen inhibition of animal growth.…”
Section: Growth Ratementioning
confidence: 95%
“…Several reports have shown a close relationship between the hormones insulin (Murshed et al 2022) and IgF (Jia et al 2021) on growth rate. Furthermore, a publication by Purba et al (2022) suggested that insulin and IGF are a group of anabolic hormones, capable of stimulating the growth of muscle tissue cells. Tissue protein synthesis in muscle appears to increase with increasing concentrations of the hormone insulin (Müller et al 2022).…”
Section: Growth Ratementioning
confidence: 99%
“…Sheep are regarded as a highly significant livestock species in terms of global food production, as they offer valuable resources such as fur, meat, and goat’s milk for humans ( 1 , 2 ). Trace essential minerals, serving as essential cofactors and enzyme components in diverse biological processes, play a pivotal role in the immune, oxidative, and energy metabolism of sheep.…”
Section: Introductionmentioning
confidence: 99%